2020
DOI: 10.1016/j.bbrc.2020.08.086
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide and its fluorescent derivative inhibit the main proteases of 2019-nCoV and SARS-CoV through covalent linkage

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by 2019 novel coronavirus (2019-nCoV) has been a crisis of global health, whereas the effective vaccines against 2019-nCoV are still under development. Alternatively, utilization of old drugs or available medicine that can suppress the viral activity or replication may provide an urgent solution to suppress the rapid spread of 2019-nCoV. Andrographolide is a highly abundant natural product of the medicinal plant, Andrographis paniculata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 35 publications
3
85
0
Order By: Relevance
“…An enzyme-based assay and in silico modeling prediction showed andrographolide could inhibit the main protease (M pro ) activities of SARS-CoV-2 with an IC 50 of 15 μM. 26 , 29 When compared to our finding, the IC 50 from the M pro enzyme-based assay was 10 times higher, implying that andrographolide probably functions through multiple targets as previously predicted by in silico models. 25 28 It has been proposed that andrographolide is involved in multiple steps of the viral life cycle including viral entry, genetic material replication, and protein synthesis and inhibits the expression or function of the mature proteins.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…An enzyme-based assay and in silico modeling prediction showed andrographolide could inhibit the main protease (M pro ) activities of SARS-CoV-2 with an IC 50 of 15 μM. 26 , 29 When compared to our finding, the IC 50 from the M pro enzyme-based assay was 10 times higher, implying that andrographolide probably functions through multiple targets as previously predicted by in silico models. 25 28 It has been proposed that andrographolide is involved in multiple steps of the viral life cycle including viral entry, genetic material replication, and protein synthesis and inhibits the expression or function of the mature proteins.…”
Section: Resultssupporting
confidence: 75%
“… 25 28 Recently, Shi et al applied an enzyme-based assay to demonstrate an inhibitory effect of andrographolide against SARS-CoV-2 main protease (M pro ). 29 Furthermore, our group has utilized a phenotypic cell-based immunofluorescent assay (IFA) to reveal the anti-SARS-CoV-2 effect of A. paniculata extract and andrographolide in African green monkey kidney cells (Vero E6). 30 Notably the anti-SARS-CoV-2 activity of A. paniculata extract and andrographolide has never been elucidated in infected human lung epithelial cells.…”
mentioning
confidence: 99%
“…In several studies, various docking methods and software consistently predicted negative binding energy (ie, indicating potential for good binding affinity) for andrographolides and its derivatives when docked against SARS-CoV-2 spike protein-angiotensin converting enzyme (ACE)−2 complex, spike protein, ACE-2 receptor, 3-chymotrypsin-like protease (3CL pro , previously known as SARS-CoV-2 main protease (M pro )), and RNA dependent RNA polymerase (RdRp). [29][30][31][32][33][34][35][36][37][38][39] 3CL pro was the most commonly investigated target in 9 out of 11 in silico studies (81.8%). [30][31][32][34][35][36][37][38][39] Negative binding energy was also predicted for andrographolide and its derivatives when docked against SARS-CoV-2 papain-like protease (PL pro ) 30 and nucleocapsid protein binding domain 37 by single studies.…”
Section: Results: Antiviral Evidence Against Sars-cov-2mentioning
confidence: 99%
“…51 The versatility of andrographolide as a SARS-CoV-2 antiviral is demonstrated by its potential to bind to several important targets at various stages of viral attachment, replication, and host-pathogen interactions. [29][30][31][32][33][34][36][37][38][39] This property may be an important advantage to any potential therapeutic agent being developed. Viral life cycle modeling studies have suggested that effective infection attenuation of repurposed drugs is more likely to be achieved when multiple segments of the viral life cycle are targeted, especially when timely administration of an antiviral in the early phases of infection is challenging in reallife settings.…”
Section: Discussion: Antiviral Evidence Against Sars-cov-2mentioning
confidence: 99%
“…Baicalin has also been investigated for the in vitro propagation of SARS-CoV in Vero-E6 cells, though no significant activity was found (EC 50 > 100 μM) [ 105 ]. Additionally, the labdane diterpene andrographolide and a semisynthetic derivative displayed inhibitory activity against 3CL pro [ 182 ], while tannic acid was found active with an IC 50 of 2.1 μΜ [ 183 ].…”
Section: Nps With Anti-hcov Potentialmentioning
confidence: 99%